(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the Preparedness of Quezon City’s Social Welfare and Development in conducting a diversion program in Barangay Kaligayahan Novaliches. Two groups from the barangay personnel and residents were selected using a purposive sampling technique based on the result of the Preparedness of Quezon City Social Welfare and Development. The findings suggest that Quezon City Social Welfare and Development is adequately prepared to conduct the diversion program in Barangay Kaligayahan. The staff members possess the necessary skills, knowledge, and training to implement the program effectively. They also have access to the necessary resources, including facilities and equipment, to support the implementation of the program. However, the study also reveals some challenges that Quezon City Social Welfare and Development may encounter in conducting the program, including the lack of coordination among stakeholders and the limited budget for program implementation. Furthermore, the study highlights the importance of community involvement and engagement in the successful implementation of the diversion program. The Barangay officials and youth offenders who participated in the study emphasized the need for more community-based interventions to address the underlying causes of youth delinquency. Overall, the study concludes that Quezon City Social Welfare and Development is adequately prepared to conduct the diversion program in Barangay Kaligayahan. However, there is a need for more collaboration and coordination among stakeholders to ensure the sustainability and effectiveness of the program. The study recommends that Quezon City Social Welfare and Development should explore more community-based interventions that involve the active participation of the community, especially the youth and their families. Additionally, there is a need to secure more funding to support the implementation of the program and ensure its long -term success.